Aldehyde dehydrogenase in solid tumors and other diseases: Potential biomarkers and therapeutic targets. Issue 1 (16th January 2023) - Xia, Jie; Li, Siqin; Liu, Suling; Zhang, Lixing
Abstract: The family of aldehyde dehydrogenases (ALDHs) contains 19 isozymes and is involved in the oxidation of endogenous and exogenous aldehydes to carboxylic acids, which contributes to cellular and tissue homeostasis. ALDHs play essential parts in detoxification, biosynthesis, and antioxidants, which are of important value for cell proliferation, differentiation, and survival in normal body tissues. However, ALDHs are frequently dysregulated and associated with various diseases like Alzheimer's disease, Parkinson's disease, and especially solid tumors. Notably, the involvement of the ALDHs in tumor progression is responsible for the maintenance of the stem‐cell‐like phenotype, triggering rapid and aggressive clinical progressions. ALDHs have captured increasing attention as biomarkers for disease diagnosis and prognosis. Nevertheless, these require further longitudinal clinical studies in large populations for broad application. This review summarizes our current knowledge regarding ALDHs as potential biomarkers in tumors and several non‐tumor diseases, as well as recent advances in our understanding of the functions and underlying molecular mechanisms of ALDHs in disease development. Finally, we discuss the therapeutic potential of ALDHs in diseases, especially in tumor therapy with an emphasis on their clinical implications. Abstract : The human aldehyde dehydrogenase (ALDH) superfamily comprises 19 isozymes and can be divided into 11 distinct families. ALDHs are a group of nicotinamide adenine dinucleotide phosphate (NADP+)‐dependent enzymes that could catalyze the reversible oxidation of endogenous and exogenous aldehydes to their corresponding carboxylic acids. However, ALDHs are frequently dysregulated and associated with various diseases like Alzheimer's disease, Parkinson's disease, and especially solid tumors. Different ALDH isoenzymes are believed to be potential biomarkers or therapeutic targets in different diseases.